Prevalence, awareness, treatment and control of high blood pressure in the elderly according to the ethnic group. Colombian survey (Colombia Medica, 2019)
Introduction: High blood pressure (HBP) is the main cardiovascular risk factor, it is more prevalent in the older adult population, and the prevalence can vary between ethnic groups.Objective: To estimate the prevalence of HBP, knowledge, treatment and control in population aged ≥60 years, resident in Colombia, according to their ethnic condition.Methods: Population sample selected by multistage sampling. Ethnicity was defined based on skin color. HBP was defined as systolic blood pressure ≥140, and/or diastolic blood pressure ≥90 mm Hg, and/or the participants’ self-report. Controlled HBP at a blood pressure value